Pengaruh Kebijakan Countercyclical Yang Dikeluarkan Oleh Otoritas Jasa Keuangan Akibat Penyebaran Covid-19 - Rani Apriani (Fakultas Hukum Universitas Islam Malang, 2023)
The covid-19 pandemic has had an impact on the global economic downturn in all types of economic business, including insurance in Indonesia. The purpose of this study was to analyze the effect of countercyclical policies issued by the Financial Services Authority due to the spread of covid-19. The method used is normative juridical which is descriptive analytical by describing the implementation and problems surrounding the effect of countercyclical policies issued by the Financial Services Authority due to the spread of covid-19. Covid-19 has had an impact on Indonesian insurance. The Financial Services Authority issues countercyclical policies for non-bank financial institutions through Letter Number S-11/D.05/2020 concerning Countercyclical Policies for the Impact of the Spread of Covid-19 for Insurance Companies. The issuance of this rule by the Financial Services Authority will affect the parties in the insurance agreement, namely the insured and the insurer.